PERANAN KEJAKSAAN DALAM IMPLEMENTASI PENEGAKAN HUKUM PERATURAN MAHKAMAH AGUNG RI NOMOR : 02 TAHUN 2012 TENTANG PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KUHP TERHADAP PENYELESAIAN TINDAK PIDANA HARTA KEKAYAAN (DALAM SISTEM PERADILAN PIDANA DI INDONESIA) - Agung Irawan (Riau Law Journal, 2019)
This study aims to find out and understand how the Duties and Authority of the Prosecutor's Office in Applying the Republic of Indonesia Supreme Court Regulation number: 02 of 2012 concerning the adjustment of minor criminal offenses and the amount of fines in the Criminal Code in relation to cases of minor criminal offenses. (Case Study of Theft Case in the Kampar District Prosecutor's Office) and What are the obstacles and obstacles faced by the Research Prosecutor in Applying the Republic of Indonesia Supreme Court Regulation No. 02/2012 concerning the adjustment of minor criminal offenses and the amount of fines in the Criminal Code in Minor Crimes in the scope of Assets. this is done sociologically, based on facts in the field. The results of the study found that the Public Prosecutor in carrying out his duties in the field of prosecution in receiving case files Investigations by the Police must carefully see whether a case is included in the category of Minor Crimes as intended by Supreme Court Regulation Number 2 of 2012 or not with various considerations that can understood by Police Investigators, of course this will give a sense of justice both to the Suspect and to victims of crime and the community at large.This study aims to find out and understand how the Duties and Authority of the Prosecutor's Office in Applying the Republic of Indonesia Supreme Court Regulation number: 02 of 2012 concerning the adjustment of minor criminal offenses and the amount of fines in the Criminal Code in relation to cases of minor criminal offenses. (Case Study of Theft Case in the Kampar District Prosecutor's Office) and What are the obstacles and obstacles faced by the Research Prosecutor in Applying the Republic of Indonesia Supreme Court Regulation No. 02/2012 concerning the adjustment of minor criminal offenses and the amount of fines in the Criminal Code in Minor Crimes in the scope of Assets. this is done sociologically, based on facts in the field. The results of the study found that the Public Prosecutor in carrying out his duties in the field of prosecution in receiving case files Investigations by the Police must carefully see whether a case is included in the category of Minor Crimes as intended by Supreme Court Regulation Number 2 of 2012 or not with various considerations that can understood by Police Investigators, of course this will give a sense of justice both to the Suspect and to victims of crime and the community at large.